Karakteristik Es Krim Ubi Jalar Ungu (Ipomoea batatas L.) Probiotik Dan Viabilitas Lacticaseibacillus paracasei RB210 Selama Penyimpanan - Gabrielle Thasya Wangsaputri; Ni Nyoman Puspawati; Sayi Hatiningsih (Itepa : Jurnal Ilmu dan Teknologi Pangan, 2026)
Despite being a popular food, commercial ice cream products frequently contain synthetic colorants and flavorings. The anthocyanin pigments found in purple sweet potatoes increase the functional value of ice cream by acting as a natural substitute for artificial coloring agents and a source of antioxidant. This functional value might also be improved by adding probiotics such as Lacticaseibacillus paracasei RB210. However, probiotic viability may decrease during processing and frozen storage. The starch in purple sweet potato has the potential to protect probiotic cells and help maintain their viability during storage. The purpose of this study was to determine whether the purple sweet potato puree to milk ratito and storage time affected the viability of Lc. paracasei RB210 and to develop probiotic purple sweet potato ice cream with the best characteristics throughout four weeks of storage. This study was conduct using a Completely Randomized Design (CRD) with two factors which were puree-to-milk ratio (0:100, 5:95, 10:90, 15:85, 20:80) and storage duration (0, 2, and 4 weeks), resulting in 15 treatment combinations with two replications (30 units). Data were analyzed using ANOVA followed by DMRT when significant. Results showed that the interaction between the two factors significantly affected anthocyanin content, hedonic scores for color, aroma, taste, texture, overall acceptance, and descriptive scores for color and taste. The purée-to-milk ratio significantly affected overrun, melting time, protein content, and antioxidant activity. Storage duration significantly affected melting time, LAB count, and antioxidant activity. The best treatment (U3M4) maintained Lc. paracasei RB210 viability with 88% overrun, 8.05 minutes melting time, 3.37% protein, 8.24 log CFU/g LAB (1.83 × 10⁸ CFU/g), 41.72% antioxidant activity, and 2.55 mg/100g anthocyanins. The ice cream had a favorable purple color, mildly distinctive sweet potato taste, pleasant aroma, and was highly liked for its texture and overall acceptance.